Opportunities to Harness Technology to Deliver HIV Prevention / Healthy Sexuality Programming to Sexual and Gender Minority Adults Living in East Africa - Ybarra, Michele; Nyemara, Novatus; Mugisha, Frank; Garofalo, Robert (AIDS and Behavior, 2021)
Because of stigmatization of and discrimination against lesbian, gay, bisexual, transgender, and other sexual and gender minority (SGM) people in East Africa, there is paucity of SGM-focused sexual health research. Technology-based outreach efforts may represent a feasible way to reach and engage this population. They also may be a way to deliver important yet sensitive sexual health information in a stigma-free, anonymous atmosphere. We explored the feasibility of recruiting and surveying East African SGM adults online, and examined their interest in technology-based sexual health programming. Over a 14-month period, 2451 respondents were surveyed. They were, on average, 26.7 years of age. Fifty-four percent identified as lesbian, gay, and/or bisexual (LGB); a similar percentage (49%) reported having sex with a same-sex partner. Sixteen percent identified as gender minority (i.e. transgender or non-binary); and 29% were assigned female at birth. Almost half (48%) of SGM adults expressed interest in an SGM-focused healthy sexuality program delivered online. Enthusiasm also was noted for email (43%) and text messaging (41%). Compared to face-to-face settings, technology-based settings were more commonly appraised as the safest mode through which one could engage in sexual health programming. People who had a same sex partner and those who identified as sexual minority were especially likely to want to engage in technology-based programs. Interest in technology-based programming was similar for adults across gender identities, sex assigned at birth, and age however. Findings suggest that technology may be an underutilized opportunity to reach and engage SGM East Africans in a safe and private manner. Given levels of acceptability indicated by SGM adults across age, sex assigned at birth, and gender and sexual identities in this study, it seems possible that technology-based sexual health and HIV prevention and intervention programs could have the potential to be transformative in East Africa.
Keywords: Technology; HIV; Sexual and Gender Minority